Problems of Islamic education in colonial and post-colonial Malaysia: An analysis based on al-Attas’s notion of knowledge - Kushimoto, Hiroko (Pertubuhan Tarekat Muktabar Malaysia (PERTAMA), 2017)
The purpose of this article is to review the history of Islamic learning and its relationship with the modern national education system in Malaysia to reveal the underlying common issue of the education in the Muslim society. Applying al-Attas’s critique of modern Muslim education and the ideas of post-colonial critique of the power behind the knowledge production and distribution, the article reveals the indifference of Muslim leaders toward the worldview behind the modern education system. Based on the analysis of a Malay Islamic journal “Pengasuh” in the early 20th century, of the process of establishment of modern religious schools and of the contemporary school textbooks for Islamic education, it shows the evidence that the Malay Islamic leaders have ignored the differences in the meaning of learning. As a result of the integration into the national education system, learning Islam was given a new meaning in the context of the national, social or the “secular” purpose of education, just as al-Attas has warned for the past four decades.